Three Male Primary Student Teachers' Intersections of Languaging and Teaching - Steven Sexton (National Research University Higher School of Economics, 2023)
Background: This paper reports on an investigation of male primary student teachers about their planning and teaching over the course of the 2021 year. Three male student teachers' experiences are presented. Purpose: This study highlights how they negotiated the intersections of self with school, identity, and gender as male student teachers. Method: In weekly semi-structured peer group discussions student teachers were asked to describe the decisions that they made in planning, to reflect on the nature of the decision-making process that they went through, and about the consequences of this process. As necessary, questions were posed to the groups to further stimulate discussions. Written notes were taken from these discussions and used in combination with visiting lecturer notes about their teaching practice. Results: It was through the combination of these classroom activities and teaching practice observations that ethnomethodology and symbolic interactionism intersected with these student teachers' self with school, identity, and gender. Ethnomethodology concerns how social order is established through social interactions while symbolic interactionism includes both verbal and non-verbal communication. It has been known that past experiences are the foundations of future experiences. The three male primary student teachers presented in this study support this assertion through their inward-looking and/or outward looking narratives. Conclusion: This study adds to our understanding of the importance of what messages schools, colleagues, and the wider community are sending to male primary teachers about their work and worth as primary teachers.